Conditions and Scale of Foreigners' Employment in Poland - Organiściak-Krzykowska, Anna; Piotrowski, Marek (Olsztyn Economic Journal, 2015)
Free movement of production factors is one of the main conditions of effective economy. This applies to capital as well as knowledge and labour. However, an influx of foreigners to the given country may lead to consequences which are compatible or incompatible with its economic and social interests. These consequences depend on the specific situation of the given country in various areas connected with the state of labour resources, economic trends and strategy, or the situation on the labour market. The principal aim of the present article is to provide an insight into the rules for offering jobs to foreigners in Poland and to describe the phenomenon of their employment based on the data aggregated by the Ministry of Labour and Social Policy. On the basis of the research conducted, a systematic increase in foreigners' employment in Poland could be observed in recent years (particularly as a part of the so-called simplified procedure applied to short-term employment). The largest group of foreigners are Ukrainians, who work mainly in agriculture, forestry, fishery, hunting, construction, retail and in household employing workers.